2016
DOI: 10.5352/jls.2016.26.4.475
|View full text |Cite
|
Sign up to set email alerts
|

New Four-herb Formula Ameliorates Memory Impairments via Neuroprotective Effects on Hippocampal Cells

Abstract: The current study was conducted to evaluate beneficial effects of a new formula (CWC-9) using four traditional Oriental medicinal herbs, Cynanchum wilfordii, Rehmannia glutinosa, Polygala tenuifolia, and Acorus gramineus, on hippocampal cells and memory function. To examine the neuroprotective effects of a new four-herb extract, cell viability, cytotoxicity, and reactive oxygen species (ROS) assays were performed in HT22 cells and behavioral tests (Morris water maze and passive avoidance retention), Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…These cells have been used to evaluate the neuroprotection activity of herbal medicines intended for the treatment of ND. A study showed that four traditional Oriental medicinal herbs protect the rat hippocampal cells from glutamateinduced toxicity by reducing the ROS production and increasing cell viability [61]. Although these cell lines provide a promising approach to evaluate the neuroprotection and neuroregeneration potential of herbal medicines, its action is limited to the animal AD, and it cannot induce the full range of deficits seen in human with AD due to lack of receptor for human Aβ peptides [59].…”
Section: Commonly Used Cell Lines For In Vitro Nd Modelmentioning
confidence: 99%
“…These cells have been used to evaluate the neuroprotection activity of herbal medicines intended for the treatment of ND. A study showed that four traditional Oriental medicinal herbs protect the rat hippocampal cells from glutamateinduced toxicity by reducing the ROS production and increasing cell viability [61]. Although these cell lines provide a promising approach to evaluate the neuroprotection and neuroregeneration potential of herbal medicines, its action is limited to the animal AD, and it cannot induce the full range of deficits seen in human with AD due to lack of receptor for human Aβ peptides [59].…”
Section: Commonly Used Cell Lines For In Vitro Nd Modelmentioning
confidence: 99%